Sosialisasi Aplikasi Sistem Cerdas Pemilihan Makanan Sehat Bagi Masyarakat Kota Lubuklinggau - Syafiul Hamidani; Robi Yanto; Ahmadi Ahmadi; , Arie Yandi Saputra (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
People's consumption patterns that tend to ignore nutritional and health aspects are one of the factors contributing to the increased risk of various non-communicable diseases. Lack of knowledge about the nutritional content of food and limited access to accurate information makes it difficult for people to make healthy food choices. With the development of digital technology, intelligent systems can be utilized as a solution to help people obtain food recommendations that meet their nutritional needs and health conditions. This community service activity aims to improve the community's knowledge and skills in choosing healthy foods through socialization and training in the use of an intelligent healthy food selection application. The activity implementation method includes planning, preparation, implementation of socialization and training, and evaluation. The activity was attended by 30 participants consisting of the general public in Lubuklinggau City. The results of the activity showed an increase in participants' understanding of nutrition from 55% to 85%, their ability to use the application from 20% to 90%, and their ability to choose healthy foods from 50% to 88%. In addition, participants responded positively to the application's ease of use and the benefits they gained during the activity. Thus, the socialization activity of the smart healthy food selection system application has proven effective in increasing public nutritional literacy and encouraging the use of digital technology to support a healthy lifestyle.